Analisis Perbaikan Proses Shipping Kursi Mobil Dalam Upaya Mengurangi Frekuensi Terjadinya Delay Delivery - M Yani Syafei; Andi Muhamad Yusuf (JIE Scientific Journal on Research and Application of Industrial System, 2019)
PT. FSI is a company engaged in the automotive sector. Increased demand and efforts to meet customer satisfaction, then encouraging companies to continue to make various improvements including the shipping department, which is to facilitate the delivery of products to customers. One of the causes of the delay in the delivery of products to customers (delay delivery) is that there is a problem in the pre-delivery process, namely the storage conveyor machine. A storage conveyor machine is a machine that connects from the results of the production process to the temporary storage of goods which are then put into trucks to be sent to consumers.The objective achieved in this study was to analyze the causes of the delay delivery in the process of shipping car seats on conveyor storage machines and make improvements to reduce the jammed base pallet frequency on the storage conveyor machine using the six sigma method. Based on the results of the research and analysis that have been carried out, it turns out that the case of the jammed base pallet on the conveyor storage machine is the cause of delay delivery to the customer and then make improvement to overcome or reduce the frequency of jammed base pallet problems on the storage conveyor machine by adding sponges to the shaft roller conveyor. The addition of sponge rolls is intended to increase power when moving base pallet between stations.